2006
DOI: 10.2355/isijinternational.46.1165
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thermal Annealing Effects on the Evolution of Coke Carbon Structure Using Raman Spectroscopy and X-ray Diffraction

Abstract: Coke is one of the important materials for ironmaking process such as blast furnace as it plays multiple roles by providing heat energy, performing the role of reducing agent and spacer for maintaining the blast furnace permeability. Due to increasing economic and environmental concerns, there is growing interest in reducing coke consumption by using innovative blast furnace operations such as accelerating coke reactions at relatively lower reactions. In an operating blast furnace, coke carbon structure is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 12 publications
7
54
0
Order By: Relevance
“…Crystallite condensation, as observed in this study, was also observed by Takagi et al [5] for chars produced at different temperatures, which was more pronounced for chars produced at 760°C and 900°C. A careful analysis of the scatter of the results reported by Kawakami et al [6], also shows an increase in inter-layer spacing between chars prepared at 900°C and 1200°C. Kuroda and Akamatu [19], Kumar and Gupta [21], Lu et al [10] and Wu et al [7] had reported that significant crystallite growth usually starts from 1600°C, with experiments conducted by these investigators, confined to temperatures above 1200°C.…”
Section: X-ray Diffraction (Xrd) Carbon Crystallite Analysesmentioning
confidence: 83%
See 1 more Smart Citation
“…Crystallite condensation, as observed in this study, was also observed by Takagi et al [5] for chars produced at different temperatures, which was more pronounced for chars produced at 760°C and 900°C. A careful analysis of the scatter of the results reported by Kawakami et al [6], also shows an increase in inter-layer spacing between chars prepared at 900°C and 1200°C. Kuroda and Akamatu [19], Kumar and Gupta [21], Lu et al [10] and Wu et al [7] had reported that significant crystallite growth usually starts from 1600°C, with experiments conducted by these investigators, confined to temperatures above 1200°C.…”
Section: X-ray Diffraction (Xrd) Carbon Crystallite Analysesmentioning
confidence: 83%
“…With the availability of advanced equipment for measurement of chemical structures such as ssNMR, XRD and high resolution TEM (HRTEM) it is expected that more reliable reaction indices could be identified for conversion under chemical reaction conditions. Some investigators have used XRD carbon crystallite analysis to study devolitalization (rapid pyrolysis) [4][5][6][7]; gasification [7][8][9]; and combustion [10,11]. It was generally found that increasing devolitalization temperature increases the structural orderliness of the resultant char carbon crystallite, which affects the lattice properties [4][5][6][7][8][9][10][11] with increasing aromaticity [4,10], and fraction of crystalline carbon [4,[6][7][8]10,11].…”
Section: Introductionmentioning
confidence: 98%
“…This is also supported by a detailed band analysis of the G-and D-band spectral region that was carried out for disordered structure materials such as coke carbon. [24] The D-peak arises as a result of resonant Raman coupling to the phonon excited by the incident photon (a double-resonance phenomenon). The dominant Raman intensity of the D-band can normally be understood in terms of symmetric breathing modes of clusters of six-fold rings.…”
Section: Raman Spectra and Line Shape Analysis Of Different Bandsmentioning
confidence: 99%
“…On the other hand, it was found that the defect of the triangle as shown by (3) did not largely react. Figure 11 shows the results of Raman spectroscopic measurements of the sample before and after the experiment (Exp-3) in comparison with the graphite and coke sample (metallurgical one 13,14) ). After the experiment, the diamond showed two broad peaks in its spectrum, which quite resembles that of coke.…”
Section: Gasification With 30 Vol%comentioning
confidence: 99%
“…After the experiment, the diamond showed two broad peaks in its spectrum, which quite resembles that of coke. The Raman spectrum of coke was precisely studied by Kawakami, et al 13,14) Coke has many kinds of carbon structures, ranging from amorphous to graphite structures. It is interesting to note that, in the course of gasification with CO 2 , the diamond surface showed almost the same structure as coke in the view point of Raman measurement.…”
Section: Gasification With 30 Vol%comentioning
confidence: 99%